Urgency Of Adaptive Leadership In Increasing The Quality Of Boarding Schools During The Covid 19 Pandemic - Ulil Azmi; Fitriyani, Fitriyani; Eri Deka Gustiar (Cita konsultindo, 2022)
Adaptive leadership is the ability of a leader or leader to be able to adapt to various conditions so as to be able to accept new alternatives in fighting for the achievement of the vision in creative ways without ignoring the goals of the organization or educational institution . The influence of the Covid 19 pandemic was felt in Islamic boarding schools in the regions. Concern about this influence is also a complaint from teachers, ustadz and Tengku in various regions. In situations and conditions like these, adaptive leadership style is very suitable to be applied in Islamic boarding schools , because adaptive leadership means leadership that is capable and intelligent in dealing with various situations and conditions. Adaptive leadership is always able to organize his personality and improve mental quality, to be involved in the process of change, always increases certainty higher, and has a better enthusiasm for learning from every point of change towards the desired reality. So that with the condition of the Covid 19 pandemic, it does not weaken a pesantren or Islamic boarding school leader in running the existing education system. So, the efforts of a leader are highly expected to find solutions to various kinds of problems that arise